2010
DOI: 10.1063/1.3299022
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility bio-organic field effect transistors with photoreactive DNAs as gate insulators

Abstract: Organic-soluble DNAs bearing chalcone moieties were synthesized by using purified natural sodium DNA. In addition to the chalcone-containing DNA homopolymer (CcDNA), a copolymer (CTMADNA-co-CcDNA) was synthesized. They were employed as gate insulators for fabricating organic thin-film transistors. An organic semiconductor (5,5′-(9,10-bis((4-hexylphenyl)ethynyl)anthracene-2,6-yl-diyl)bis(ethyne-2,1-diyl)bis(2-hexylthiophene; HB-ant-THT) was deposited on the photocrosslinked DNA-based gate insulators via a solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…The mechanism of the memorizing effect caused by the DNA gate dielectrics remains poorly understood. Some of the researchers attribute the hysteresis behavior to the mobile ion impurities [29,30]. However, Liang et al [19] demonstrated the memory window still exists even in a much lower temperature region, as shown in Figure 4.…”
Section: Dna As Functional Layers For Otftsmentioning
confidence: 99%
“…The mechanism of the memorizing effect caused by the DNA gate dielectrics remains poorly understood. Some of the researchers attribute the hysteresis behavior to the mobile ion impurities [29,30]. However, Liang et al [19] demonstrated the memory window still exists even in a much lower temperature region, as shown in Figure 4.…”
Section: Dna As Functional Layers For Otftsmentioning
confidence: 99%
“…16 Previous work on a crosslinked DNA-based biopolymer, when used as a gate insulator in a thin film transistor (TFT), contributed to the reduction of hysteresis caused by ion migration leading to enhanced device operation. 17,18 We have come up with a new crosslinking method which will be addressed later in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, organic field effect transistors, optical amplifiers 5 , conductive, semiconductive nanowires 6 , and nonlinear optical electro-optic modulators have been fabricated from DNA-based biopolymers. Such devices have demonstrated high performance that exceeds that of state-of-the-art devices made with currently available organic based materials [7][8][9][10][11] . In our study, we have already reported the organic light-emitting diodes fabricated with DNA as a template of charge transport materials and light-emitting materials 12,13 .…”
Section: Introductionmentioning
confidence: 99%